Qualitative analysis of plastic debris on beaches of Brunei Darussalam - Qaisrani, Zahid N.; Shams, Shahriar; Guo, Z. R.; Mamun, Abdullah Al (University of Tehran, 2020)
Plastic debris is one of the major environmental concerns for the coastal area of Brunei Darussalam. It reduces the aesthetic appeals of the beaches in the country. The current study investigates marine debris on six different beaches of Brunei Darussalam along the South China Sea. Plastic was found the most abundant among whole debris by number (90.02%) and by weight (39.12%). It was classified by size (micro (<5 mm), meso (5-20 mm), macro (21-100), and mega (>100 mm)), colour (transparent, coloured, white and black). Fourier Transform Infrared Spectroscopy (FTIR) was used to investigate the types of plastics and additives present in it. Statistical analysis using Minitab 17 and Kruskal-Wallis test was performed for comparison of data at different study sites. All major types of plastics were found in different forms with varying quantities from which toxic chemicals may leach out during degradation. The highest abundance by the number of plastic debris was found on Muara beach with a mean value 74.428 n/m2 ± 34.33 n/m2, while the lowest abundance was found on Lumut beach 53 n/m2 ± 20.9 n/m2. The study shows beaches used for recreational facilities are likely to have more debris as compared to other beaches.